Oxygen Reduction Reaction Activity of Nanocolumnar Platinum Thin Films by High Pressure Sputtering. Issue 13 (22nd September 2020) - Ergul-Yilmaz, Busra; Begum, Mahbuba; Yang, Zhiwei; Perry, Mike L.; More, Karren L.; Macauley, Natalia; Borup, Rod L.; Karabacak, Tansel
Abstract : Nanocolumnar platinum thin films (Pt-TFs) were produced by high pressure sputtering (HIPS) and investigated as oxygen reduction reaction electrocatalysts for polymer electrolyte membrane fuel cells. Conventional high-density Pt-TF prepared by low pressure sputtering was also studied for comparison. Pt-TFs were deposited on a microporous layer (MPL)-like surface composed of carbon particles to mimic catalyst-coated gas diffusion electrodes. Electron microscopy imaging revealed that HIPS Pt-TFs developed a cauliflower-like columnar microstructure, which originated from a shadowing effect during HIPS. This shadowing effect is enhanced on the rough surface of the MPL-like carbon that leads to the nano-cauliflower formation. With this approach, we also aimed to relate the catalyst performance obtained by benchtop tests directly to membrane electrode assembly test results. The electrochemically active surface area of Pt-TFs increased from 10 to 19 m 2 g −1 with increasing sputter pressure. Specific activity of conventional high-density and nanocolumnar films were similar at ∼600 μ A cm −2, which is likely due to their similar crystal grain sizes, >5 nm. On the other hand, mass-specific (MA) activity values increased from ∼0.06 A/mgPt for conventional Pt-TF to ∼0.13 A/mgPt for HIPS Pt-TFs, which is consistent with the columnar microstructure of HIPS films providing a better catalyst utilization compared to conventional Pt-TF.